How do shooting athletes select strategies? Emotional intensity and time constraints influence shooters` emotion regulation choice - Liu, H.; Zhou, L.; Wang, H.; Jiang, Y. (Journal of Clinical Sport Psychology, 2025)
In high-precision shooting sports, emotional dysregulation among athletes has become increasingly prevalent. Emotion Regulation Choice (ERC), the ability to select the most appropriate strategy for emotional management, is critical for athletes. However, research on ERC within sports contexts remains limited. This study investigates how emotional intensity and time constraint shape athletes` ERC in shooting sports. Study 1 explored athletes` choices between distraction and reappraisal under varying emotional intensities using the Geneva Affective Pictures and ERC paradigm. Study 1 found a significant preference for reappraisal under low intensity and a trend toward distraction under high intensity. Study 2, using sport-specific emotional pictures and introducing time constraints, showed that distraction was consistently favored under the time-constrained condition, whereas intensity effects reappeared under the time-abundant condition. This research contributes to the application of ERC in sports and offers valuable insights for developing emotion regulation training programs for athletes.